THE ART OF GIVING AND ITS PLACE IN TODAY'S MUSIC-CULTURAL LIFE - Toshmatova Kumush Aliboy qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article talks about the art of bakshilik, one of the genres of Uzbek folk music, and its place and importance in today's musical and cultural life. Also, the article describes the attention paid to the art of singing, its development trends, the formation of epics and other similar information on modern compositional art.